Women's Iddah Provisions In The Understanding Of Islamic Family Law Study Program Students Uin Antasari Banjarmasin - Bagus Pambudi (Interdisciplinary Explorations in Research Journal, 2024)
ABSTRACT Iddah is a transition period after divorce and before remarriage, whether divorced or alive. Islam has paid a lot of attention to the discussion of iddah which can be studied from the Qur’an, as-Sunnah, and al-Ijma’. UIN Antasari Banjarmasin itself also paid attention to this study, so that this study also became learning material for its students. Thus, this research will discuss idddah in the understanding of Islamic Family Law students at UIN Antasari Banjarmasin. The method used is fieldwork collected by direct interviews with student speakers. The research results show that Islamic Family Law students at UIN Antasari Banjarmasin can be said to have a good understanding of iddah. They can explain well the definition, objectives and laws of iddah. Their understanding, which is still considered moderate, is regarding the iddah periods for each condition. Keywords: Iddah, Understanding, Student. ABSTRAK Iddah merupakan masa transisi setelah bercerai dan sebelum menikah lagi, baik cerai mati ataupun cerai hidup. Islam telah banyak memberi perhatian dalam bahasan iddah yang dapat dipelajari dari al-Qur’an, as-Sunnah, dan al-Ijma’. UIN Antasari Banjarmasin sendiri juga memberikan perhatiannya dalam kajian ini, sehingga kajian ini turut menjadi bahan belajar oleh mahasiswanya. Dengan demikian, penelitian ini akan membahas mengenai idddah dalam pemahaman mahasiswa Hukum Keluarga Islam UIN Antasari Banjarmasin. Metode yang digunakan ialah lapangan yang dikumpulkan dengan wawancara langsung bersama mahasiswa narasumber. Hasil penelitian menunjukkan bahwa mahasiswa Hukum Keluarga Islam UIN Antasari Banjarmasin dapat dikatakan memiliki pemahaman yang baik mengenai iddah. Mereka dapat menjelaskan dengan baik mengenai definisi, tujuan, dan hukum iddah. Adapun pemahaman mereka yang masih dianggap sedang ialah mengenai masa-masa iddah masing-masing kondisi. Kata Kunci : Iddah, Pemahaman, Mahasiswa.